2023
DOI: 10.48550/arxiv.2302.11083
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Obfuscation of Pseudo-Deterministic Quantum Circuits

Abstract: We show how to obfuscate pseudo-deterministic quantum circuits, assuming the quantum hardness of learning with errors (QLWE) and post-quantum virtual black-box (VBB) obfuscation for classical circuits. Given the classical description of a quantum circuit Q, our obfuscator outputs a quantum state | Q that can be used to evaluate Q repeatedly on arbitrary inputs.Instantiating the VBB obfuscator for classical circuits with any candidate post-quantum indistinguishability obfuscator gives us the first candidate con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…Similarly, Alagic et al demonstrated the impossibility of universal virtual black-box obfuscation in quantum settings, but quantum obfuscation can still be achieved by particular obfuscation methods for specific functions or circuits. In 2023, Bartusek et al [24] implemented a quantum obfuscation scheme for polynomial-sized pseudo-deterministic quantum circuits. In particular, this scheme can obfuscate the circuit implementing Shor's algorithm.…”
Section: Impossibility and Possibilitymentioning
confidence: 99%
“…Similarly, Alagic et al demonstrated the impossibility of universal virtual black-box obfuscation in quantum settings, but quantum obfuscation can still be achieved by particular obfuscation methods for specific functions or circuits. In 2023, Bartusek et al [24] implemented a quantum obfuscation scheme for polynomial-sized pseudo-deterministic quantum circuits. In particular, this scheme can obfuscate the circuit implementing Shor's algorithm.…”
Section: Impossibility and Possibilitymentioning
confidence: 99%